Pengembangan E-LKS Interaktif Mata Pelajaran Bahasa Inggris dengan Menggunakan Model ADDIE di Sekolah Dasar Negeri Karawaci Baru 4 Kota Tangerang - Asih Rosnaningsih; Elsa Ardelia; Tia Anggestin (Universitas Persada Indonesia YAI, 2021)
This study aims to developThis research used Research and Development (R&D) research with the ADDIE modeldevelopment framework. The research subjects were Teachers of SDN Karawaci Baru 4Kota Tangerang. The research instruments used was a feasibility test by Experts andQuestionnaire. Based on the results of the questionnaire obtained a score of 87.28% so itcan be concluded that the Multimedia-based Interactive E-LKS is